EFFECTIVENESS OF REPLACING Artemia sp. FEED WITH FERMENTED PASTE FEED ON THE GROWTH AND SURVIVAL OF STRIPED CATFISH LARVAE (Pangasionodon hypopthalmus) PUSTINA STRAIN - Rizqy Putra Perdana; Netti Aryani; Nur Asiah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
Striped catfish (Pangasianodon hypophthalmus) in Riau is known as a commodity with bright prospects for cultivation, given increasing market demand aligned with community needs and its affordable price. This study was conducted from April 28 to June 7, 2025, at the Fish Breeding and Improvement Laboratory, Faculty of Fisheries and Marine Sciences, Universitas Riau. The objective of this study was to determine the optimal timing for switching from Artemia sp. feed to fermented paste feed to enhance the growth and survival rate of Pustina strain striped catfish larvae. The method used was an experimental method with five treatments and three replicates (15 experimental units) with a stocking density of 75 fish/tank and with treatments AR 5 T 5 PBF 30 (Artemia sp. 5 days + silkworms 5 days + Fermented Paste Feed 30 days), AR 5 T 7 PBF 28 (Artemia sp. 5 days + silkworms 7 days + Fermented Paste Feed 28 days), AR 5 T 9 PBF 26 (Artemia sp. 5 days + silkworms 9 days + Fermented Paste Feed 26 days), AR 5 T 11 PBF 24 (Artemia sp. 5 days + silkworms 11 days + Fermented Paste Feed 24 days), AR 5 T 13 PBF 22 (Artemia sp. 5 days + silkworms 13 days + Fermented Paste Feed 22 days). The best treatment was AR 5 T 13 PBF 22 (Artemia sp. 5 days + silkworms 13 days + Fermented Paste Feed 22 days), which produced absolute weight growth of 2.49±0.037e, absolute length growth of 5.99±0.62e, specific growth rate of 17.16±0.05e, and survival rate of 87.11±2.03a.